Increase in immune activation, vascular endothelial growth factor and erythropoietin after an ultramarathon run at moderate altitude - Schobersberger, W.; Hobisch-Hagen, P.; Fries, D.; Wiedermann, F.; Rieder-Scharinger, J.; Villiger, B.; Frey, W.; Herold, M.; Fuchs, D.; Jelkmann, W. (Immunobiology, 2000)
The present study was performed to investigate the effects of exhaustive long lasting exercise at moderate altitude on the time course of serum immunomodulatory peptides, vascular endothelial growth factor (VEGF) and serum erythropoietin (EPO). Thirteen well trained runners participated at the Swiss Alpine Marathon of Davos (distance 67 km, altitude difference 2300 m). Interleukin-6 was significantly elevated in the first 2h after the run. In contrast, tumor necrosis factor-alpha and both soluble tumor necrosis factor-a receptors I and II were increased after exercise termination and showed sustained serum concentrations the following days. Neopterin, a serum marker for the activation of the cellular immune system, was increased until day two after the run. Immediately after the run VEGF was significantly elevated and further increased 2.4-fold until day five post exercise (p = 0.005). EPO was also increased after exercise but reached its maximum 2 h after the run (2-fold increase; p = 0.004) and decreased thereafter. The main findings of our study are that prolonged strenuous exercise at moderate altitude induced a significant long lasting increase in serum VEGF and EPO which was accompanied by an activation of the immune system. Immunobiology 2000 Apr;201(5):611-20